Risk Aversion, Indivisible Timing Options, and Gambling - Henderson, V; Hobson, D (2013)
In this paper we model the behavior of a risk-averse agent who seeks to maximize expected utility and who has an indivisible asset and a timing option over when to sell this asset. Our main contribution is to show that, contrary to intuition, optimal behavior for such a risk-averse agent can include risk-increasing gambles. For example, a manager with a choice over when to disinvest from a project, a private homeowner with a property to sell, or an employee with a grant of American-style stock options may be better off taking positions in other assets with zero Sharpe ratio that are uncorrelated with the underlying project, house, or stock price risk. The results have wider implications for the modeling and interpretation of portfolio optimization problems involving American-style timing decisions. © 2013 INFORMS.